FLOWING COLORS IN THE PAINTINGS OF CONTEMPORARY EXPERIMENTAL ARTIST AFZAL PATHAN: REFLECTIONS OF RURAL LANDSCAPE AND SOCIAL SCIENCE AND THEIR INTERRELATIONSHIP - Gupta, Rakhi; Bharadwaj, Kumkum; Chouhan, Sadhna (International Journal of Research -GRANTHAALAYAH, 2026)
The overall development of art is the result of a historical and social process. Artists continuously develop their artistic journey through new experiments and explorations, establishing new dimensions. Currently, experimentation is clearly prevalent not only in India but throughout the world. Change is a continuous process, and a sensitive and aware society is guiding ancient traditions and values ​​towards new directions through art. This transformation in art is evident in contemporary art. The new art created through experimentation, which is original and innovative, is called contemporary experimental art. Art is a mirror of society. The contemporary art of every era expresses social sentiments, values, traditions, problems, and activities of that particular time through paintings. This research paper presents the artistic vision, experimental style, emotions, and ideas of the 20th-century contemporary experimental artist Afzal Pathan through his use of colors and forms in his paintings. Human relationships, social consciousness, the complexities of life, and natural forms are depicted through Afzal Pathan’s abstract expression. Afzal Pathan, a contemporary experimental artist residing in Dewas city, Madhya Pradesh, uses oil paints in a manner similar to watercolors and employs a restrained color scheme, often using muted colors such as brown, black, and earthy tones. This reflects his seriousness and contemplative personality. This study also clarifies that his abstract painting is not only for aesthetic purposes but also serves as a powerful medium for social commentary. His works depict humanity, coexistence, and inner conflicts, along with natural forms such as birds and rocks. Through this research paper, Afzal Pathan’s art establishes a broad tradition of modern Indian abstract painting and maintains its unique identity. In conclusion, his abstract oil paintings reflect society, rural life, nature, colour communication, and relationships between these elements.